The impact of gender medicine on neonatology: the disadvantage of being male: a narrative review - Claudio Migliori; Marta Braga; Virginia Siragusa; Maria Cristina Villa; Livio Luzi (BMC, 2023)
Abstract This narrative non-systematic review addresses the sex-specific differences observed both in prenatal period and, subsequently, in early childhood. Indeed, gender influences the type of birth and related complications. The risk of preterm birth, perinatal diseases, and differences on efficacy for pharmacological and non-pharmacological therapies, as well as prevention programs, will be evaluated. Although male newborns get more disadvantages, the physiological changes during growth and factors like social, demographic, and behavioural reverse this prevalence for some diseases. Therefore, given the primary role of genetics in gender differences, further studies specifically targeted neonatal sex-differences will be needed to streamline medical care and improve prevention programs.